An attempt to adopt aggregation-induced emission to study organic–inorganic composite materials. Issue 26 (21st June 2018) - Li, Weili; Yao, Wei; Tebyetekerwa, Mike; Tang, Jijun; Yang, Shengyuan; Zhu, Meifang; Hu, Rong; Qin, Anjun; Tang, Ben Zhong; Xu, Zexiao
Abstract : With aggregation-induced emission, the morphology and properties of the prepared organic-inorganic composites coating can be studied intuitively and systematically. In addition, the obtained fluorescent property made the coatings fit a wide range of applications. Abstract : Owing to the hybrid nature of organic–inorganic composite coatings, when applied, they can combine the merits of both components and thus make such coatings fit a wide range of applications. However, due to the property differences in these composites, the strategy to obtain well dispersed organic–inorganic coatings is not yet straightforward and it is of great importance for their implementation and to obtain advanced properties such as mechanical properties, corrosion-resistance, aging resistance performance, and others. In this regard, still, even the characterization and direct visualization of the making up the organic–inorganic composites are not easy tasks. Herein, a strategy to visual characterize organic–inorganic composite coatings via aggregation-induced emission (AIE) is reported. Briefly, the approach involved first designing and synthesizing a novel water dispersed AIEgen whose AIE effect was systematically analyzed. Then, inorganic Na + -montmorillonite (MMT) was introduced to the synthesized AIEgen via the ion exchange method in order to make the inorganic MMT adopt fluorescence properties. The modified MMT fluorescence property was beneficial for the imaging and characterization of the macro-dispersed MMT in the cured coatings. As an essential addition to the study, the responses of the modified MMT cured composite coatings to temperature and corrosive material erosion were studied in detail. An account of the responses demonstrated the possible application of such modified coatings in high-performance smart paints.